Training & development - Biech, Elaine (--For dummies., 2022)
Retain outstanding talent with a successful training and development program One of the best ways to retain great talent in your business is to deliver a strong training and development program-and this book gives you the tools to do just that. Featuring the latest strides in talent development, such as social learning, hybrid training, creating videos, and more, it arms you with everything you need to upskill employees to be more effective, productive, satisfied, and loyal. - Develop a robust training and development program - Foster a supportive and innovative work environment - Use mentoring, coaching, and informal learning effectively - Align learning to your organization's needs Engage your employees with a motivating training program using the helpful guidance in Training & Development For Dummies!